MALANG CORRUPTION WATCH SEBAGAI GERAKAN MASYARAKAT SIPIL DALAM MEMBANGUN BUDAYA ANTI-KORUPSI DI DAERAH - Fahdian Rahmandani; Samsuri Samsuri (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
Corruption is a problem that threatens various sectors, such as politics, education, economy, culture, and health. At the area level, corruption cases are a threat that is difficult to detect because of the absence of ad-hoc institutions in conducting surveillance. Therefore, it takes an independent civil society at the area level to enable monitoring and voiced the idea of anti-corruption. This study aims to determine the role of non-governmental organizations namely Malang Corruption Watch in building an anti-corruption culture in Malang Raya. The method used in writing this article is a literature study. The results of this study indicate that Malang Corruption Watch is a non-governmental organization that has an independent nature. In overcoming the problem of communal corruption, Malang Corruption Watch provides citizenship education to the people’s in the form of people political education, public schools, citizen forums, community groups guarding public services, campaigning for anti-corruption movements, and anti-corruption schools to increase the critical power of citizens in addressing the middle public problems happen. Furthermore, there are several posts complaints that are provided so that citizens can easily express their aspirations to realize an anti-corruption culture